2020
DOI: 10.1002/adfm.201909504
|View full text |Cite
|
Sign up to set email alerts
|

Stimuli‐Responsive MXene‐Based Actuators

Abstract: MXenes, a member of 2D inorganic compounds that contain few-atom-thick layers of transition metal carbides, nitrides, and polar surface functional groups, are extraordinary materials for many applications including stimuliresponsive actuators. Here, an extensive review on MXene-based actuators in comparison with other 2D materials-based actuators is reported, highlighting the main differences in view of chemical structure, mechanical properties, and electrical functionalities. First, since MXenes are newcomers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
115
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 159 publications
(116 citation statements)
references
References 247 publications
1
115
0
Order By: Relevance
“…[28] They have numerous applications in a variety of fields ranging from energy materials, lubricating additives, nanocomposites, etc. owing to excellent properties; [5,8,13,[28][29][30][31][32][33] MXene-based composites have already been used in many fields such as electromagnetic shielding, [32,34,35] electronics, [36] electrical and thermal conductors, [33,37,38] environmental remediations, [39] supercapacitors, [40,41] fire safety materials, [42] photocatalysts, [43,44] sensors, [10,45] batteries, [46] self-healing composites, [40,47] water purifications, [44,48] antibacterial materials, [49] actuators, [50] and other advanced materials and structures. [8,29,51] For instance, Kang et al [36] developed Ti 3 C 2 MXene reinforced epoxy nanocomposite to enhance thermal and electrical performance wherein they found that the addition of 1.0 wt% few-layer Ti 3 C 2 MXene increases the thermal conductivity to 0.587 W m −1 K −1 , attaining 141.3% improvement compared with that of unreinforced sample.…”
Section: Introductionmentioning
confidence: 99%
“…[28] They have numerous applications in a variety of fields ranging from energy materials, lubricating additives, nanocomposites, etc. owing to excellent properties; [5,8,13,[28][29][30][31][32][33] MXene-based composites have already been used in many fields such as electromagnetic shielding, [32,34,35] electronics, [36] electrical and thermal conductors, [33,37,38] environmental remediations, [39] supercapacitors, [40,41] fire safety materials, [42] photocatalysts, [43,44] sensors, [10,45] batteries, [46] self-healing composites, [40,47] water purifications, [44,48] antibacterial materials, [49] actuators, [50] and other advanced materials and structures. [8,29,51] For instance, Kang et al [36] developed Ti 3 C 2 MXene reinforced epoxy nanocomposite to enhance thermal and electrical performance wherein they found that the addition of 1.0 wt% few-layer Ti 3 C 2 MXene increases the thermal conductivity to 0.587 W m −1 K −1 , attaining 141.3% improvement compared with that of unreinforced sample.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, various properties of MXenes have been revealed by both theoretical simulations and experimental investigations, predicting that they can be significantly influenced by their intrinsic compositions and post‐treatments. Consequently, 2D MXene materials have been extensively used in various fields, such as energy storage devices, [ 34 ] biomedicine, [ 49 ] EMI shieldings, [ 37 ] catalysts, [ 31 ] sensors, [ 20 ] and other fields. [ 14,29 ] The property modifications of MXenes are still ongoing to further enhance the performance of MXene‐based devices.…”
Section: Preparations and Properties Of Mxenesmentioning
confidence: 99%
“…[ 13–17 ] In light of these fascinating characteristics, 2D materials demonstrate vast potential applications in the fields of chemistry, materials science, and nanotechnology. [ 18–21 ]…”
Section: Introductionmentioning
confidence: 99%
“…These photothermal actuators are generally composed of a bilayered structure with light absorption ability: a passive layer with a small coefficient of thermal expansion (CTE) and a thermal expansion layer with a large CTE. Carbon-based materials such as carbon black, [54] carbon nanotube (CNT), [28,55] graphite, [56] graphene oxide (GO), [57][58][59] and MXene [60][61][62] are often used as light absorption layers. Polymers having large CTE such as poly(dimethylsiloxane) (PDMS), [48] polyimide (PI), [63] polycarbonate (PC), [49] biaxially oriented polypropylene (BOPP), [64] poly(vinylidene fluoride) (PVDF), [65] polyethylene (PE) [66] serve as thermal expansion layers.…”
Section: Volume Expansionmentioning
confidence: 99%